Response of Arbuscular Mycorrhizal Fungi in Combination on Growth and Nutrient Uptake in Bambusa nutans - Verma, R. K.; , Jamaluddin (Indian Forester, 2004)
The response of three different inocula of arbuscular mycorrhizal (AM) fungi was studied on growth, biomass, phosphorus (P) and nitrogen (N) uptake and per cent root colonization in Bambusa nutans seedlings. The seedlings were raised as per routine nursery procedure in unsterilized soil mix. Mix AM inocula were used to inoculate the seedlings and comprised: (1) Acaulospora scrobiculata, Glomus mosseae, Scutellospora heterogama and S. pellucida, (2) Acaulospora sp. 2, A. scrobiculata, Gigaspora sp., Glomus mosseae, and Scutellospora pellucida, (3) A. laevis, Acaulospora sp., Gigaspora sp., S. pellucida. The first two inocula were isolated from bamboo root segments and the third from teak rhizosphere soil. The improvement in growth parameters is correlated with per cent root colonization of seedlings by AM fungi. Arbuscular mycorrhization by selected AM fungi constitutes in important approach for subsequent growth and development of Bambusa nutans seedlings.